Brain size evolution in pipefishes and seahorses: the role of feeding ecology, life history and sexual selection - Tsuboi, Masahito; Lim, Adam Chee Ooi; Ooi, Boon Leong; Yip, M.Y.; Chong, Ving Ching; Ahnesjö, Ingrid; Kolm, Niclas (Wiley, 2016)
Brain size varies greatly at all taxonomic levels. Feeding ecology, life history and sexual selection have been proposed as key components in generating contemporary diversity in brain size across vertebrates. Analyses of brain size evolution have, however, been limited to lineages where males predominantly compete for mating and females choose mates. Here, we present the first original data set of brain sizes in pipefishes and seahorses (Syngnathidae) a group in which intense female mating competition occurs in many species. After controlling for the effect of shared ancestry and overall body size, brain size was positively correlated with relative snout length. Moreover, we found that females, on average, had 4.3% heavier brains than males and that polyandrous species demonstrated more pronounced (11.7%) female-biased brain size dimorphism. Our results suggest that adaptations for feeding on mobile prey items and sexual selection in females are important factors in brain size evolution of pipefishes and seahorses. Most importantly, our study supports the idea that sexual selection plays a major role in brain size evolution, regardless of on which sex sexual selection acts stronger.